Wednesday
March 29, 2017

Post a New Question

Posted by on .

3n/(n2 -7n + 10) - 2n/(n2-8n+15)
thanks

  • Math - ,

    n^2-7n+10 = (n-2)(n-5)
    n^2-8n+15 = (n-3)(n-5)
    LCD = (n-2)(n-3)(n-5), so we have

    [3n(n-3) - 2n(n-2)] / ((n-2)(n-3)(n-5))
    = (3n^2-9n-2n^2+4n) / (...)
    = (n^2-5n) / (...)
    = n(n-5) / (n-2)(n-3)(n-5)
    = n / (n-2)(n-3)
    = 3/(n-3) - 2/(n-2)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question